2021
DOI: 10.1111/eip.13260
|View full text |Cite
|
Sign up to set email alerts
|

Identifying pathways to early‐onset metabolic dysfunction, insulin resistance and inflammation in young adult inpatients with emerging affective and major mood disorders

Abstract: Aim: Young people with common mood disorders face the prospect of shortened life expectancy largely due to premature cardiovascular disease. Metabolic dysfunction is a risk factor for premature cardiovascular disease. There is an ongoing debate whether metabolic dysfunction can be simply explained by weight gain secondary to psychotropic medications or whether shared genetic vulnerability, intrinsic immunemetabolic disturbances or other system perturbations (e.g. dysregulated sympathetic nervous system, circad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Much attention in recent years has focused on the extent to which the risk of metabolic disturbances, and most fundamentally of glucose and insulin, are prevalent among those treated for depressive and other mood disorders (Osimo et al, 2021;Scott et al, 2019;Tickell et al, 2022). Public concern has also focused on the increased rates of premature mortality in those with chronic depression and other major mental disorders, with a significant proportion of that risk being due to early-onset cardiovascular disease (particularly among women).…”
Section: Contextmentioning
confidence: 99%
“…Much attention in recent years has focused on the extent to which the risk of metabolic disturbances, and most fundamentally of glucose and insulin, are prevalent among those treated for depressive and other mood disorders (Osimo et al, 2021;Scott et al, 2019;Tickell et al, 2022). Public concern has also focused on the increased rates of premature mortality in those with chronic depression and other major mental disorders, with a significant proportion of that risk being due to early-onset cardiovascular disease (particularly among women).…”
Section: Contextmentioning
confidence: 99%
“…• the detection of immune activation in younger clinical and population-based cohorts suggests that such activation may not simply be correlates of chronicity or treatment; • detailed exploration of more specific markers in smaller subgroups of cohorts with depression or other major mood disorders (e.g., atypical or bipolar depression) indicates higher rates of perturbations; • we see increasing reports of the linking of immune activation with other pathophysiological processes, including metabolic disturbance or circadian rhythm disturbance (Hickie et al 2018;Lamers et al 2020;Tickell et al 2021) adaptive immune responses and the brain's intrinsic nonspecific immune effector cells, microglia (Banati 2003;North et al 2021). This peripheral-central cross-talk may underlie secondary progressive neuropathological changes in various mental disorders; and • we witness significant advances in the understanding of basic brain cell-immune signalling interactions and their neurobehavioural and neuropsychological consequences (Bower and Kuhlman 2023;Capuron and Miller 2011).…”
Section: Contextmentioning
confidence: 99%
“…This retrospective cohort study builds on our previous cross‐sectional study highlighting the high prevalence of overweight and obesity, and elevated updated homeostatic model assessment for insulin resistance (HOMA2‐IR) scores in a subset of young people presenting for mental health care (Scott et al, 2019 ). Additional work on inpatients admitted to a young adult mental health unit found that HOMA2‐IR scores were cross‐sectionally linked to the prescription of mood stabilizers and BMI, but not to specific diagnoses, other medication types or the number of prescribed medicines (Tickell et al, 2021 ). Accordingly, the aim of this retrospective study was to expand on these findings to examine the cardiometabolic characteristics associated with clinical stage, cross‐sectionally and longitudinally, in a cohort of young people accessing early intervention services for mental health care.…”
Section: Introductionmentioning
confidence: 99%